The Mediating Role of Innovative Work Behavior on the Leader Member Exchange and Job Satisfaction at Indonesian Food & Beverage Services Industry during Covid 19 - Dewi Shanty; Justine Tanuwijaya; Valentina Happy Vanesa; Stefanus Sadana (Budapest International Research and Critics University, 2022)
Indonesian tourism, especially in the Greater Jakarta area, is not only famous for buildings, monuments, but with high diversity, Jabodetabek offers delicious culinary tours that serve special foods from all corners of the archipelago. To be able to face stiff competition in the business world, from the point of view of the current food and beverage provider organization leaders need to innovate in their work to produce employees who are satisfied with their work, so the purpose of this study is to analyze the effect of LMX on Job Satisfaction mediated by Innovative work behavior by using The quantitative method is a questionnaire via google form with a total of 249 respondents. Sample is 249 respondents. The analytical method used is SEM - AMOS 24. The results showed that LMX had a significant positive effect on IWB and Job Satisfaction , while IWB has no effect on Job Satisfaction and also IWB cannot mediate the effect of LMX on Job Satisfaction.